Media Illustration of Storybooks and Video Barcodes in an Effort to Improve Listening Ability of Kindy B Students - Siti Fatimah; Ida Yeni Rahmawati; Betty Yulia Wulansari (Universitas Muhammadiyah Ponorogo, 2022)
This research aims to (1) develop a media story book illustration and barcode videos in an effort to increase the listening ability to the kindy B’s students in Mutiara Hati Kindergarten. (2) find out the difference between before and after using a media story book illustration and a barcode video. The study used the research method research and development (rd). Data is collected using authentic test assessments, interviews and angkets. Qualitative data are analysed in a descriptive way from interviews and expert advice on validation, the quantitative data comes from the expert validation and authenticated testing methods of pre-experimental experimentation in the form of one group preposttest. The results of this study are (1) a media story book illustration and a barcode video entitled